Problematika Program Siaran Dakwah Islam: Studi pada Radio Republik Indonesia (RRI) Kota Sorong - Rahmat, Rahmat; Suharmoko, Suharmoko (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2021)
This study aims to determine the da'wah broadcast programs and what factors are the obstacles in the LPP RRI Islamic da'wah broadcast program, Sorong city. The method used is qualitative. Data were collected through documentation, interviews, observations, and literature. Furthermore, the data obtained were analyzed to get a conclusion. The results showed that LPP RRI Sorong City organized 8 (eight) Islamic Da'wah (SDI) broadcast programs. Furthermore, the problems that arise in the implementation of broadcast programs are pretty diverse, including 1) the consistency of the SDI program participant group, 2) the schedule of the presenter's changes, 3) the discipline of the presenters in filling the event, 4) the budget is inadequate, 5) the competence of the creative team, and 6) development and presence of competitors. Therefore, excellent and competitive management is needed in providing quality and professional broadcast services.